National Mainstreaming Workshop on Climate Risk Management in Agricultural Extension (CRMAE) for Ethiopia - Belay, Berhanu; Bulo, Million; Ambaw, Gebermedihin; Amha, Yosef; Demissie, Teferi; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
Climate change is a pressing global challenge, with agriculture being one of the most vulnerable sectors. Adapting to and mitigating its impacts requires multifaceted approaches, including integrating climate education into curricula to build knowledge, skills, and resilience among stakeholders. Embedding Climate Knowledge Products (CKPs) into educational programs is crucial for fostering climate adaptation and mitigation strategies tailored to diverse communities. A gap analysis conducted in universities and Agricultural Technical and Vocational Education and Training (ATVET) colleges revealed the need to incorporate CKPs into existing curricula. In response, the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA), the Ethiopian Meteorological Institute (EMI), the Ministry of Agriculture (MoA), and the Ministry of Labor and Skills (MoLS) collaborated to pilot the integration of CKPs into the crop production course of the ATVET curriculum. This initiative demonstrated the feasibility and value of scaling up CKP integration across other agricultural disciplines. A workshop involving experts from AICCRA, EMI, MoA, and MoLS introduced CKPs into four key programs: Animal Production, Animal Health, Natural Resource Management, and Irrigation and Drainage. The updated curricula, incorporating CKPs into Occupational Standards, Teacher Training, and Learning Manuals (TTLM), have been submitted to MoLS for implementation. This initiative underscores the importance of equipping ATVET graduates as the future agricultural workforce with the tools to support smallholder farmers and pastoralists in building climate resilience. Recommendations include expanding CKP integration across all agricultural curricula and providing capacity-building training for educators. Furthermore, collaboration with the Ministry of Education is suggested to embed climate literacy from kindergarten to higher education, including a foundational climate basics course for first-year students.